Neutropthil-to-Lymphocyte Ratio as a Predictor of Postsurgical Intraabdominal Abscess in Children Operated for Acute Appendicitis - Delgado-Miguel, Carlos; Muñoz-Serrano, Antonio J.; Núñez, Vanesa; Estefanía, Karla; Velayos, María; Miguel-Ferrero, Miriam; Barrena, Saturnino; Martínez, Leopoldo (Frontiers in Pediatrics, 2019)
Aim of the study: Postoperative intra-abdominal abscess (PIAA) is a frequent and severe complication of acute appendicitis (AA) with peritonitis. The neutrophil-to-lymphocyte ratio (NLR) is an inflammatory marker that has been related to the development of peritonitis; however, its diagnostic role in predicting PIAA has not been evaluated. This is the first study that analyzes the usefulness of NLR as a predictor of PIAA in children operated for AA. Material and Methods: Retrospective observational study in children operated for AA in our institution during 2017-2018. Patients aged under 5 years or with incomplete laboratory determinations at hospital admission (blood count, C-reactive protein and fibrinogen) were excluded. Demographic and laboratory parameters and the development of PIAA were analyzed. NLR was calculated by dividing the absolute number of neutrophils by the absolute number of lymphocytes. By means of ROC curves, we determined the sensitivity and specificity of the different laboratory parameters to predict the development of PIAA. Results: A total of 388 patients aged 10.5±2.9y were included. Twenty (5.2%) developed PIAA. NLR presented an area under the curve (AUC) of 0.85, significantly higher than the determination of leukocytes (AUC 0.69, p<0.001), neutrophils (AUC 0.74, p<0.001), fibrinogen (AUC 0.68, p<0.001) and C-reactive protein (AUC 0.73, p<0.001). We estimated the optimal cut-off point of NLR>10.5, with a sensitivity of 85% and a specificity of 75.2%. Conclusions: NLR is the laboratory parameter with the highest sensitivity and specificity for predicting the development of PIAA in children operated for AA. It can be useful as a predictor of worse postoperative course.